1997
DOI: 10.1128/mcb.17.5.2550
|View full text |Cite
|
Sign up to set email alerts
|

Reduced O Glycosylation of Sp1 Is Associated with Increased Proteasome Susceptibility

Abstract: Sp1 is a ubiquitously expressed transcription factor that is particularly important for the regulation of TATA-less genes that encode housekeeping proteins. Most growth factors and receptors are also encoded by such genes. Sp1 is multiply O glycosylated by covalent linkage of the monosaccharide N-acetylglucosamine (O-GlcNAc) to serine and threonine residues. Based on an earlier observation that growth factor gene transcription can be regulated by glucose and glucosamine in vascular smooth muscle cells, we dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
346
0
3

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 402 publications
(360 citation statements)
references
References 49 publications
11
346
0
3
Order By: Relevance
“…However, our data provide the first direct correlation between decreased O‐GlcNAc levels and impaired leptin production in vivo. Our findings are in accord with studies showing that reduced O‐GlcNAc lowers levels of Sp1 in cells6f, 13 and that OGT plays a pivitol role in fat tissues 14. Notably, these data also suggest that regulation of leptin by O‐GlcNAc is bidirectional in vivo as overexpression of OGT,3 knockout of OGA,15 and metabolic upregulation of UDP GlcNAc levels16 all increase leptin expression.…”
supporting
confidence: 92%
“…However, our data provide the first direct correlation between decreased O‐GlcNAc levels and impaired leptin production in vivo. Our findings are in accord with studies showing that reduced O‐GlcNAc lowers levels of Sp1 in cells6f, 13 and that OGT plays a pivitol role in fat tissues 14. Notably, these data also suggest that regulation of leptin by O‐GlcNAc is bidirectional in vivo as overexpression of OGT,3 knockout of OGA,15 and metabolic upregulation of UDP GlcNAc levels16 all increase leptin expression.…”
supporting
confidence: 92%
“…The cellular content of the transcription factor Sp1, involved in the regulation of TGFβ1 transcription [31], are up-regulated by PKC activation [32]. Furthermore hexosamines promote Sp1 O-linked N-acetylglucosamine glycosylation [33], which stabilizes this transcription factor, increasing its cellular concentrations [34]. Several other studies have proposed a role of the HBP in PKC activation in different cell types [19,35,36,37], and PKC has been shown to mediate glucose-induced p38-MAPK activation [38], confirming our results in control transfected cells.…”
Section: Discussionmentioning
confidence: 99%
“…Our preliminary results indicate that hSug1 does not interact with this target domain of Sp1 (results not shown). We have also shown that increased modification of proteins by OGlcNAc is associated with Sp1 stabilization [4] and that nuclear extract from glucosamine-treated cells fails to degrade recombinant Sp1 [33]. However, hSug1 is not modified by O-GlcNAc even in cells that had been treated with glucosamine, and hSug1 cannot restore the activity of the proteasomes derived from glucosamine-treated cells.…”
Section: Discussionmentioning
confidence: 82%
“…Previous studies have shown that Sp1 is rapidly degraded by the proteasome under the conditions of glucose-starvation and stimulation by cAMP [4]. However, the control of this degradation process is largely unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation